Schwann cell precursors represent a neural crest‐like state with biased multipotency. (11th July 2022) - Kastriti, Maria Eleni; Faure, Louis; Von Ahsen, Dorothea; Bouderlique, Thibault Gerald; Boström, Johan; Solovieva, Tatiana; Jackson, Cameron; Bronner, Marianne; Meijer, Dies; Hadjab, Saida; Lallemend, Francois; Erickson, Alek; et al.
Abstract: Schwann cell precursors (SCPs) are nerve‐associated progenitors that can generate myelinating and non‐myelinating Schwann cells but also are multipotent like the neural crest cells from which they originate. SCPs are omnipresent along outgrowing peripheral nerves throughout the body of vertebrate embryos. By using single‐cell transcriptomics to generate a gene expression atlas of the entire neural crest lineage, we show that early SCPs and late migratory crest cells have similar transcriptional profiles characterised by a multipotent "hub" state containing cells biased towards traditional neural crest fates. SCPs keep diverging from the neural crest after being primed towards terminal Schwann cells and other fates, with different subtypes residing in distinct anatomical locations. Functional experiments using CRISPR‐Cas9 loss‐of‐function further show that knockout of the common "hub" gene Sox8 causes defects in neural crest‐derived cells along peripheral nerves by facilitating differentiation of SCPs towards sympathoadrenal fates. Finally, specific tumour populations found in melanoma, neurofibroma and neuroblastoma map to different stages of SCP/Schwann cell development. Overall, SCPs resemble migrating neural crest cells that maintain multipotency and become transcriptionally primed towards distinct lineages. Synopsis: The identity and potential of Schwann cell precursors (SCP) in the developing embryo remains poorly understood. This transcriptional, temporal and spatial single‐cell profiling resource uncovers SCPs as a multipotent source of neural crest‐like cells. Single‐cell transcriptome profiling of genetically‐labelled neural crest and SCP lineages cells in the E9.5 to E12.5 mouse embryo defines SCPs as a multipotent neural crest‐like cell. SCPs and neural crest converge into a common Sox8 + transcriptional state characterized by multiple biases towards downstream fates. Fate decisions are structured in a conserved three‐step mechanism consisting in co‐activation, repulsion of transcriptional programs and cell fate commitment. Terminal neuro‐muscular junction glial progenitor identity is defined by a unique transcriptional code. Abstract : A transcriptional, temporal and spatial single‐cell profiling resource uncovers Schwann cell progenitors as a multipotent source of neural crest‐like cells in the developing mouse embryo.